2014
DOI: 10.3389/fimmu.2014.00595
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Preterm Birth as a Polymicrobial Disease: An Overview of the Uterine Microbiome

Abstract: Infection is a leading cause of preterm birth (PTB). A focus of many studies over the past decade has been to characterize microorganisms present in the uterine cavity and document any association with negative pregnancy outcome. A range of techniques have been used to achieve this, including microbiological culture and targeted polymerase chain reaction assays, and more recently, microbiome-level analyses involving either conserved, phylogenetically informative genes such as the bacterial 16S rRNA gene or who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
87
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 97 publications
6
87
0
13
Order By: Relevance
“…The role of the microbiome in the uterus and cervix is largely unknown, but the implications for human health, reproduction, fertility, and the development of human fetuses are immense [31]. Consistent with other studies characterizing the uterine bacterial community using next generation sequencing, we demonstrated that the uterine bacterial community is comprised mostly of a Bacteroidetes core, with a large percentage of Firmicutes, specifically Lactobacillus sp.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The role of the microbiome in the uterus and cervix is largely unknown, but the implications for human health, reproduction, fertility, and the development of human fetuses are immense [31]. Consistent with other studies characterizing the uterine bacterial community using next generation sequencing, we demonstrated that the uterine bacterial community is comprised mostly of a Bacteroidetes core, with a large percentage of Firmicutes, specifically Lactobacillus sp.…”
Section: Discussionsupporting
confidence: 73%
“…It is becoming apparent that other key members of the microbiome like fungi and viruses may play a key role in human health and disease [31] and understanding these dynamics will be imperative if we are to improve these conditions. Future studies will characterize other members of the microbiome to understand how endometriosis alters these communities.…”
Section: Discussionmentioning
confidence: 99%
“…После того, как стало ясно, что полость матки не стерильна, как счи-талось ранее, а колонизирована самыми различными микроорганизмами, многие стали относить этот факт к причине преждевременных родов [40,41]. В связи с этим в настоящее время разрабатывается «гипотеза преждевременных родов как полимикробной болезни» [42]. В частности, такие бактерии, как Ureaplasma sр.…”
Section: влияние микробиома на генотип человекаunclassified
“…В частности, такие бактерии, как Ureaplasma sр. и Fusobacterium sp., обнаруживались в матке в значи-тельной степени при неблагоприятных исходах бере-менности [42]. Предположительно маточный микробиом может вызывать эпигенетические регуляции, приводя-щие к преждевременным родам.…”
Section: влияние микробиома на генотип человекаunclassified
“…Although multiple studies demonstrate that individual infectious agents and a community of infectious agents could contribute to SPTB, it remains unclear how these changes in microbiota cause SPTB. 6 Sequential changes in the microbiota during the pregnancy likely are important in either initiating inflammation or suppressing protective factors, resulting in rupture of membranes; however, our understanding of the role of microbiota in SPTB is rather limited. Therefore, research to characterize the entire microbiome present in vaginal and placental tissues is important and may lead to a better understanding of the role of bacteria in SPTB.…”
mentioning
confidence: 99%